The Effects of Physical Activity on Drug Pharmacokinetics and Efficacy and Their Relevance in Sports Doping - vika putri; vania syakira; kayla bachmid (Universitas Negeri Surabaya, 2026)
Background: Physical exercise brings about physiological adaptations that may influence drug absorption, distribution, metabolism and excretion (ADME) and thus therapeutic efficacy and interpretation of anti-doping testing. Interest in exercise-drug interactions is expanding, but the research base is still piecemeal and mostly limited to specific classes of drugs and anti-doping situations. Objective: This narrative review aimed to summarize the existing evidence of the effects of physical activity on drug pharmacokinetics and therapeutic efficacy and implications for sports doping. Methods: Using PubMed database, a narrative review was performed to identify original studies published in the English language in the last 10 years. We included human studies investigating the influence of exercise on medication pharmacokinetics, therapeutic effect or anti-doping significance. Ten articles published between 2022 and 2025 were included in the narrative synthesis after title, abstract and full-text screening against pre-defined eligibility criteria.Results: The reviewed studies showed consistent evidence that physical activity alters the pharmacokinetic processes by changing physiological factors such as blood flow, hydration status, renal function and metabolic activity, leading to interindividual differences in drug disposition and therapeutic response. These effects were more pronounced for inhaled β 2 -agonists and non-steroidal anti-inflammatory medications and could affect the assessment of urine drug concentrations in the context of anti-doping tests. Metabolite profiling and enantioselective analysis are examples of new pharmacometric approaches that have improved the differentiation between therapeutic use of drugs and prohibited administration.Conclusion: Physical activity is an important determinant of pharmacokinetic variability with major implications for therapeutic efficacy and anti-doping interpretation. The combination of exercise physiology and pharmacokinetic evidence may lead to a more customized medication and to more accurate and equitable decision making in doping control.